A qualitative focus group discussion study on the experiences of Certified Nurses in Dementia Nursing related to effective staff education - Hiromi Taneichi; Ryoko Rokkaku (Wiley, 2020)
Abstract Aim To explore the experiences of Certified Nurses in Dementia Nursing (DCNs) concerning the effective education of staff in acute hospitals. Background In Japan, the number of inpatients with dementia who need medical care continues to increase. DCNs play an important role in educating medical staff about dementia care in acute hospitals. However, there is a lack of a clear understanding in this regard. Design A qualitative design using a thematic analysis. Methods Data were extracted from a focus group discussion conducted with 10 DCNs working in 10 different acute hospitals in central Japan. Participants answered semi‐structured, open‐ended questions about their experiences related to effective staff education. Categories, subcategories and themes were created. This study complied with the Standards for Reporting Qualitative Research. Results The two themes identified were "building a foundation for dementia care education" and "continuous support based on practical processes."